THEORETICAL ANALYSIS OF THE EFFICIENCIES OF THE ENERGY CHAIN ELEMENTS IN THE CASE OF THE TRANSITION TO ELECTRIC VEHICLES - Florin Gabriel POPESCU; Dragos PASCULESCU; Răzvan SLUSARIUC; Adina TATAR; Teodora LAZAR (Fiabilitate şi Durabilitate)
This paper aims to prove that the subject of transition to electric vehicles being a bad decision concerning efficiency, is not founded on clear grounds. So it was shown in a theoretical approach, how efficiencies for the elements in the chain of extraction, processing and distribution of different energies add up to a more clearer image of this transition that is already taking place.